Uniqueness of Solutions to a Nonlinear Elliptic Hessian Equation - Siyuan Li (Journal of Applied Mathematics)
Through an Alexandrov-Fenchel inequality, we establish the general Brunn-Minkowski inequality. Then we obtain the uniqueness of solutions to a nonlinear elliptic Hessian equation on Sn.